The impact of age, education and seniority on motivation of employees - Hitka, Miloš; Balážová, Žaneta (Business: Theory and Practice, 2015)
Motivation can be changed significantly in dependence on meeting human needs, life situations, internal and external environment, etc. It is caused by different factors which affect motivation in different ways. These factors do not act separately but they are a part of mutually connected network of specific relations. In the paper we show the possibility of the impact of age, education and seniority on the motivation of employees. The level of employee motivation and employee performance can be influenced by means of their detailed knowledge.